TINJAUAN MA’HAD AL- ZAYTUN TERKAIT PENINGKATAN INDEKS PEMBANGUNAN MANUSIA BERDASARKAN PERATURAN DAERAH KABUPATEN INDRAMAYU DAN SIYASAH DUSTURIYAH - Supriyatno, Supriyatno; Ngainnur Rohmah, Siti; Sajali, Munawir (Cahaya Ilmu Bangsa, 2024)
The Human Development Index (HDI) in Indonesia, especially in the field of education, has shown significant development over the past 10 years. HDI in education is measured through indicators such as average years of schooling, expected years of schooling, and literacy rate. The purpose of this research is to review Ma'had Al-Zaytun in Improving Human Development Index Based on Indramayu Regency Regional Regulation Number 8 of 2015 and Siyasah Dusturiyah. The author uses a library research method with a legal research approach conducted in a normative juridical manner. The data sources used are primary data sources, namely Indramayu Regency Regional Regulation Number 8 of Indramayu Regency Regional Regulation Number 8 of 2015, the book of Legal Science in the knot of Siyasah Dusturiyah Reflections on the theory and practice of Constitutional Law in Indonesia by Ali Akbar Abaib Mas Rabbani Lubis, M..H, and the book Al-Zaytun Source of Inspiration by Drs. Ch. Robin Simanullang, and secondary data sources, namely, books, journals, documents, and so on. The result of this research is Ma'had Al-Zaytun Review in Human Development Index Improvement Based on Indramayu Regency Regional Regulation Number 8 Year 2015 By paying attention to health needs, economic welfare, and religious values, Al-Zaytun supports the formation of strong, disciplined, and responsible characters in students. The commitment to a decent standard of living, health, and the integration of religious education ensures that students not only acquire academic knowledge, but also moral and social capabilities that are useful for personal life and positive contributions to the wider community and Ma'had Al-Zaytu Review in improving Human development Index based on Siyasah Dusturiyah plays an important role in improving the Human Development Index (HDI) in its region by meeting basic needs and empowering its community. Through the synergy between education, health, and economy, Al-Zaytun makes a real contribution to sustainable welfare, proving its dedication in creating a prosperous society. Kata kunci: Human Development Index, Education, Regional